A ratiometric dual luciferase reporter for quantitative monitoring of pre-mRNA splicing efficiency in vivo - Guo, Bin (J Biol Chem, 2021)
Precursor messenger RNA (pre-mRNA) splicing is critical for cell growth and development, and errors in RNA splicing frequently cause cellular dysfunction, abnormal gene expression, and a variety of human diseases. However, there is currently a lack of reliable systems to noninvasively monitor the mRNA splicing efficiency in cells and animals. Here, we described the design of a genetically engineered ratiometric dual luciferase reporter to continuously quantify the changes in mRNA splice variants in vivo. This reporter system is encoded within a single polypeptide but on separate exons, thus generating two distinct luciferase signals derived from spliced and unspliced mRNAs. With this reporter, the two kinds of luciferase in the same individual can minimize the influence of indirect factors on splicing, and the ratio of these two luciferase intensities represents the dynamic splicing efficiency of pre-mRNA. Our study offers a convenient and robust tool for the screening and identification of small molecules or trans-acting factors that affect the efficiency of specific splicing reactions.